Determining the Effects of a 12-Week Moderate Intensity Circuit Exercise Program on Body Composition and Physical Fitness among Overweight Women of Working Age - Sarocha Namboonlue; Ananya Dechakhamphu; Monthicha Raksilp (OVS LLC, 2024)
Objectives. The study aimed to examine the effects of a 12-week moderate-intensity circuit exercise program on body composition and physical fitness among overweight women of working age. Materials and methods. Twenty-nine overweight women of working age were divided into two groups: the control group (CG, n = 14) had a normal daily life, and the moderate intensity circuit exercise group (MICE, n = 15) underwent training that included 3 sessions of MICE (40-50 seconds followed by 60 seconds of rest for each exercise and 90 seconds of recovery between sessions at 64-76% of maximum heart rate). The training was conducted for 60 minutes per day, three days per week. Body composition and physical fitness were measured before (2 days prior) and after (2 days post) a 12-week training period.  Results. After the 12-week training, the MICE showed a considerable improvement in a number of key health indicators, including body weight, BMI, fat mass, skeletal muscle mass, visceral adipose tissue, total energy expenditure, resting energy expenditure, waist circumference, and waist-to-hip ratio (-0.65%, -0.73%, -2.16%, 2.53%, -7.12%, 10.85%, 0.71%, -3.13%, and -2.67%, respectively, p < 0.05) when compared to the CG. Similarly, the MICE demonstrated a significantly larger improvement in the sit and reach test, the back extension test, the hand grip strength of the right hand, hand grip strength of the left hand, leg strength, the 60-second chair stand test (also known as sit-to-stand test), and the maximum oxygen consumption (18.98%, 16.53%, 10.69%, 7.68%, 9.97%, 26.25%, and 8.87%) compared to the CG (-4.10%, -1.19%, -0.26%, -1.53%, -1.44%, 0.24%, and -0.70%), respectively. Conclusions. Moderate-intensity circuit exercise has been found to have positive effects on improving body composition and physical fitness in overweight working women. Thus, the implementation of MICE with appropriate sessions, resting, duration, and training periods can achieve maximum benefit.